Effectiveness of an Ayurvedic Formulation (Allergy Rakshak Avaleha) Alone and in Combination (with Allergy Rakshak Ghee) for Managing Allergic Rhinitis: An Open-label Randomized Controlled Study (International Journal of Ayurveda and Pharma Research, 2025)
Allergic rhinitis is a common health concern worldwide, and Ayurveda offers potential alternatives to manage its symptoms and underlying causes. Objectives: This study evaluated the efficacy and safety of Allergy Rakshak Avaleha alone and in combination with Allergy Rakshak Ghee. Materials and Methods: An open-label, randomized controlled study was conducted on participants aged 18 to 65 with allergic rhinitis. Participants were randomly assigned to three groups: Group I received Allergy Rakshak Avaleha (½ spoon twice daily), Group II received Allergy Rakshak Avaleha (½ spoon twice daily) and Allergy Rakshak Ghee (2 drops in each nostril twice daily), and Group III received standard therapy with levocetirizine (5mg) and montelukast (10mg) once daily for 28 days. The primary outcomes were the changes in Total Nasal Symptom Score (TNSS), IgE levels, and eosinophil count at the end of the treatment (EoT), and at the 1-month follow-up. The secondary outcomes included changes in quality of life (QoL) and adverse events. Results: A total of 240 participants (80 per group) were enrolled in the study. All groups demonstrated a significant reduction (p